1994
DOI: 10.1088/0305-4470/27/19/025
|View full text |Cite
|
Sign up to set email alerts
|

Solutions of the quantum Yang-Baxter equation with extra nonadditive parameters

Abstract: We present a systematic technique to construct solutions to the Yang-Baxter equation which depend not only on a spectral parameter but in addition on further continuous parameters. These extra parameters enter the Yang-Baxter equation in a similar way to the spectral parameter but in a non-additive form.We exploit the fact that quantum non-compact algebras such as U q (su(1, 1)) and type-I quantum superalgebras such as U q (gl(1|1)) and U q (gl(2|1)) are known to admit non-trivial one-parameter families of inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 21 publications
0
84
1
Order By: Relevance
“…2 [46]. There are three irreps which could be described by the symbols (1|2|1|0|0), (0|2|4|2|0) and (0|0|1|2|1).…”
Section: Appendix B Alternative Notation With Su(1|2) Symmetrymentioning
confidence: 99%
“…2 [46]. There are three irreps which could be described by the symbols (1|2|1|0|0), (0|2|4|2|0) and (0|0|1|2|1).…”
Section: Appendix B Alternative Notation With Su(1|2) Symmetrymentioning
confidence: 99%
“…It is worth to compare this construction with the one in [41]. In this reference the affinization of the R-matrix for a quantum deformation of the SU(1|2) group was considered.…”
Section: The Su (1|2) S-matrix and Crossing Transformationsmentioning
confidence: 99%
“…We note that the Hamiltonian in Ref. [26] differs from the bulk part (24), but that they are related to each other by a canonical transformation. Nevertheless, it will be shown that this transformation does not change the Bethe-ansatz equations in the bulk.…”
Section: The Solutions Of the Graded Rementioning
confidence: 99%